Sclerotherapy with 6% polidocanol solution in patients with placenta accreta - Ricardo Mauricio Malagón Reyes; Rubén Castorena de Ávila; María de Jesús Ángeles Vázquez; César Augusto Núñez Monteagudo; Hugo Mendieta Zerón (Elsevier, 2016)
Objective: Placenta accreta is one of the main obstetrical complications worldwide. The aim of this study was to report the experience of managing placenta accreta with a 6% polidocanol solution sclerotherapy. Materials and Methods: We selected patients between 37 weeks of gestation and 38 weeks of gestation, diagnosed with placenta accreta, treated at the Maternal Perinatal Hospital "Monica Pretelini Sáenz", Toluca, Mexico, during the period from November 2013 to August 2014. The surgical technique has two steps: (1) fundic-arciform caesarean section followed by a 6% polidocanol sclerosing solution through a 6Fr neonatal feeding tube upon its reaching the placental bed; (2) total abdominal hysterectomy with internal hypogastric artery ligation. Results: Data were collected from 11 patients with a mean age of 33.9 years (range, 26-42 years) and 2.8±0.6 days of hospitalization in the obstetrical intensive care unit. The majority of patients were classified as having pregnancies at an advanced age. All women were multigravidas. Bleeding volume exhibited a range between 2.5 L and 3 L without any case of neonatal death but one mother died because of coagulopathy. Conclusion: We conclude that the technique that we are reporting is feasible for implementation in obstetric hospitals, with technical and economic feasibility.